UJI EFEKTIVITAS SARI BUAH KURMA (PHOENIX DACTYLIFERA) TERHADAP JUMLAH TROMBOSIT MENCIT JANTAN (MUS MUSCULUS L) YANG DIBERI KOTRIMOKSAZOL - PUTRI NADIA; YENITA YENITA; CUT MOURISA; ISRA THRISTY (LP2MTBM MAKARIOZ, 2023)
Date palm suspension (Phoenix dactylifera) is a processed product from date palm, which has various ingredients that are beneficial for health. There was a study about the effectiveness of date palm suspension which aims to determine the effectiveness of date palm suspension to increasing the number of platelets in male mice (Mus musculus L) that given cotrimoxazole. This research use an experimental study with